Does Health Education Really Matter? Evaluating the Role of Health Education in Improving Anemia Knowledge in Adolescent Girls - Ayu, Windri Dewi; Setyawati, Anita; Jaelani, Ahmad (Multidiscience : Journal of Multidisciplinary Science, 2025)
Anemia remains a significant global health issue, particularly among adolescents, where its prevalence threatens both individual well-being and national development. This study evaluates the impact of health education on improving anemia knowledge among 32 adolescent girls at SMPN 2 Majalengka. Using a quasi-experimental approach, pretest and posttest questionnaires assessed participants' knowledge before and after a structured health education program. The intervention included lectures and discussions covering anemia's definition, symptoms, risk factors, impacts, prevention, and treatment. Results revealed a notable improvement in knowledge, with the proportion of respondents scoring in the "good knowledge" category increasing from 65.6% in the pretest to 84.4% in the posttest. The greatest improvement in understanding anemia management was observed, rising from 46.9% to 75.0%. These findings underscore the importance of systematic and well-structured health education in enhancing adolescents' understanding of anemia and promoting informed health decisions. Future efforts should prioritize developing interactive and accessible health education programs for broader adolescent populations. Further research with larger sample sizes and diverse methodologies is recommended to generalize findings and explore additional factors, such as family support and healthcare access, that influence the effectiveness of health education interventions.